Konsumsi dalam lensa Islam antara kebutuhan dan keinginan - dzikrullooh, rahmania08 ramadhani (Maliki Interdisciplinary Journal, 2025)
This article discusses the concept of consumption in Islam by highlighting the fundamental difference between needs and wants. In a modern era filled with materialism and consumerist trends, Muslims are faced with the challenge of managing consumption wisely according to religious teachings. In Islam, needs include essential elements such as food, clothing, shelter and education, while wants are the urge to have additional goods or experiences that are often unnecessary. The principles of qanaah (contentment), moderation and sharing form the basis of Islamic guidance to maintain a balance between the mundane and the spiritual, preventing excessive consumptive behavior. The article also discusses the negative impact of unbridled consumption on individuals, society and the environment, and how Islam provides simple and sustainable lifestyle solutions that bring blessings and serenity. By applying these principles, Muslims can live a more balanced and responsible life.